Animal models for meniscus repair and regeneration‡. (27th May 2013) - Deponti, Daniela; Giancamillo, Alessia Di; Scotti, Celeste; Peretti, Giuseppe M.; Martin, Ivan
Abstract: The meniscus plays an important role in knee function and mechanics. Meniscal lesions, however, are common phenomena and this tissue is not able to achieve spontaneous successful repair, particularly in the inner avascular zone. Several animal models have been studied and proposed for testing different reparative approaches, as well as for studying regenerative methods aiming to restore the original shape and function of this structure. This review summarizes the gross anatomy, function, ultrastructure and biochemical composition of the knee meniscus in several animal models in comparison with the human meniscus. The relevance of the models is discussed from the point of view of basic research as well as of clinical translation for meniscal repair, substitution and regeneration. Finally, the advantages and disadvantages of each model for various research directions are critically discussed. Copyright © 2013 John Wiley & Sons, Ltd.